Knowledge, attitudes, and practices (KAP) towards airborne isolation precautions among dental students and interns: A cross-sectional study - Pavani Bellamkonda; Hina Ahmed; Gautam Singh; Manojkumar Sachidanandan; TC Harini; Abdulsalam S. Alshammari; J Suresh Babu; C Swarnalatha; Abhishek Singh Nayyar (Journal of Family Medicine and Primary Care)
Background: There is a high possibility of cross-infections within the dental clinics given the nature of treatment procedures performed in the dental set-ups. Hence, interrupting this chain of transmission of infections within the dental clinics is an important part of routine dental practice including infections that are airborne and has significantly higher chances of transmission and that may have serious sequelae. The active transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) held responsible for the coronavirus disease-19 (COVID-19) pandemic, was, also, declared to occur mainly through the respiratory system. In similar context, very few of the studies have raised similar concerns regarding a general lack of awareness among dental students and interns as well as other healthcare providers. The objective of the present study was to assess the knowledge, attitudes, and practices (KAP) towards droplet and airborne isolation precautions among dental students and interns. Methods: The present study was conducted in a cross-sectional study design between October 2022 and December 2022, while the physical questionnaire survey instrument distributed among a total of 236, 3rd and 4th year dental undergraduate students and interns, comprised of 11 closed-ended questions for the assessment of KAP among dental students and interns towards droplet and airborne isolation precautions as illustrated by the guidelines prescribed by the Centers for Disease Control and Prevention (CDC). The data obtained was entered into excel sheets and subjected to statistical analysis. Results: The means of the KAP scores among participants were calculated as 8.74 ± 2.13, 49.06 ± 7.17, and 4.18 ± 1.24 respectively, in the present study. Also, a significant positive correlation was observed between the KAP scores among the participants, with the correlations being statistically significant when compared between the Knowledge–Attitudes scores (P = 0.03), the Knowledge–Practices scores (P = 0.04), and highly significant between the Attitudes–Practices scores (P = 0.001). Conclusions: From the results obtained, it was concluded that dental students and interns were well aware of the necessary precautions and guidelines towards droplet and airborne isolation precautions, though on close observation, it was observed that despite adequate knowledge and attitudes scores, practices scores were comparatively low.